Interaktivitas Netizen 24 Jam Pasca Deklarasi Bacapres AMIN - Sanjaya, Mochammad Lucky Trita; Nasvian, Moch Fuad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The 2024 election will elect a new president after Jokowi served for two terms. In the 2024 election, the Nasdem and PKB parties are nominating the pair Anies Baswedan - Muhaimin Iskandar as candidates for President and Vice President. The candidacy of AMIN's running mate invited debate. This research analyzes netizen reactions in comments on the content of recorded YouTube broadcasts of four Indonesian news channels - TvOneNews, MerdekaDotCom, METRO TV, and KOMPASTV - on the live broadcast of the declaration of Anies Baswedan and Muhaimin Iskandar as 2024 presidential candidates. The focus of this research data is using comments in the first 24 hours after declaration of couple Anies Baswedan and Muhaimin Iskandar. This research uses thematic analysis and reveals four main themes from the comment analysis are: supporters of other politicians, uninspiring politicians, established politicians, and national pride, which reflects a variety of perspectives. Anonymity on YouTube allows for the explicit expression of opinions, emotions, and socio-political affiliations. This highlights the participatory nature of social media in facilitating political discussions. However, increasing interactivity does not necessarily result in quality discussions. Further analysis of the substance of comments is needed to examine the qualities that shape online political discourse in Indonesia. This study provides an initial mapping of reactions for future researchers to build using sentiment or network analysis. The results of this research also underline the importance of understanding public discourse in a political context considering the widespread use of social media as a campaign tool.